Singapore perspectives 2014 differences - Mathews, Mathew.; Gee, Christopher.; Chiang, Wai Fong. (World Scientific Pub. Co., 2015)
Singapore's demographic diversity was the driving force for the country's founding leaders as they forged a nation. They sought to navigate the many differences in the country's ancestral, social and cultural affiliations even as they embarked on the urgent task of nation-building. A decade into the new century, many of the country's traditional understandings of differences are being challenged, even as new differences, spawned by immigration, new media and globalisation, emerge. The Singapore Perspectives 2014 conference considered the consequences of both historical and emergent differences, based on the understanding that race, language, religion, economic status, age and countries of origin will continue to shape Singapore's society and economy. The conference proceedings contain contributions from prominent speakers such as Singapore Minister of State for Education Sim Ann, Associate Professor Kwok Kian Woon, Dr Leslie Teo, Professor David Chan and the points of debate on the question whether consensus or contest will underpin Singapore's future from Professors Kishore Mahbubani and Chua Beng Huat.